The art of procrastination a guide to effective dawdling, lollygagging and postponing, or, getting things done by putting them off - Perry, John 1943- (HighBridge Audio, 2012)
This charming and accessible audio educates, entertains, and illuminates a universal subject. Procrastinators will be relieved to learn that actually you can accomplish quite a lot while procrastinating.